Vitamin D deficiency in athletes: Laboratory, clinical and field integration - Ip, T. S. T.; Fu, S. C.; Ong, M. T. Y.; Yung, P. S. H. (Asia-Pacific Journal of Sports Medicine, Arthroscopy, Rehabilitation and Technology, 2022)
Vitamin D deficiency is highly prevalent in athletes. Increased utilisation and storage depletion may be key contributing factor. We found a higher prevalence of vitamin D inadequacy (deficiency/ insufficiency) in power than endurance sport athletes, which may be related to vitamin D utilisation and reserve in skeletal muscles.